2020
DOI: 10.31557/apjcp.2020.21.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy with MiRNA-Mediated Targeting of Mcl-1 Promotes the Sensitivity of Non-Small Cell Lung Cancer Cells to Treatment with ABT-737

Abstract: interaction between pro-apoptotic and anti-apoptotic B-cell lymphoma-2 (Bcl-2) family proteins. Anti-apoptotic proteins including Bcl-2 itself, Mcl-1 (myeloid cell leukemia-1), Bcl-w, Bcl-xL, and Bfl-1/A1 promote

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…By using a series of biochemical, pharmacological and genetic approaches, we not only demonstrated in this study that MCL-1 up-regulation mediates apoptosis resistance in arsenic and BaP co-exposure-transformed cells, but also showed that down-regulating MCL-1 protein levels in the co-exposure-transformed cells significantly reduces their CSC-like property and tumorigenicity. Previous studies showed that down-regulating MCL-1 protein levels sensitizes lung cancer cells to ABT-737-induced apoptosis 34 , 35 . Our above findings are thus important, not only because they indicate that MCL-1 up-regulation plays a critical role in arsenic and BaP co-exposure-induced tumorigenesis, but also because they suggest that strategies of targeting MCL-1 could be effective in preventing and treating lung cancer resulting from arsenic and BaP co-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…By using a series of biochemical, pharmacological and genetic approaches, we not only demonstrated in this study that MCL-1 up-regulation mediates apoptosis resistance in arsenic and BaP co-exposure-transformed cells, but also showed that down-regulating MCL-1 protein levels in the co-exposure-transformed cells significantly reduces their CSC-like property and tumorigenicity. Previous studies showed that down-regulating MCL-1 protein levels sensitizes lung cancer cells to ABT-737-induced apoptosis 34 , 35 . Our above findings are thus important, not only because they indicate that MCL-1 up-regulation plays a critical role in arsenic and BaP co-exposure-induced tumorigenesis, but also because they suggest that strategies of targeting MCL-1 could be effective in preventing and treating lung cancer resulting from arsenic and BaP co-exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In apoptotic conditions, the pro-apoptotic members such as Bak and Bax form a homodimer, leading to the change in the mitochondrial outer membrane permeability (MOMP), release of cytochrome c from mitochondria, and subsequently activation of caspases-3, -6 and -7. The anti-apoptotic proteins such as Bcl-2 and Mcl-1, by heterodimerising with Bak and Bax, inhibit apoptosis (Shahverdi et al, 2020a;Shahverdi et al, 2020b). Fludarabine induces apoptosis in vitro systems and in primary CLL cells by inhibiting several enzymes involved in DNA and RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fludarabine-Sensitivity in CLL-CII Cells by the members of the Bcl-2 family proteins including the pro-survival members and the pro-apoptotic members (Shahverdi et al, 2020a;Shahverdi et al, 2020b). Upregulation of prosurvival Bcl-2 family members such as Bcl-2 and Mcl-1 is associated with resistance to treatment with fludarabine, chlorambucil and rituximab, as well as shorter overall survival in CLL patients.…”
Section: Mirna-mediated Knock-down Of Bcl-2 and Mcl-1 Increasesmentioning
confidence: 99%
“…ABT-737 and Bcl-2 antisense oligonucleotides were developed to trigger apoptosis in the case of NSCLC [45]. Considering the role of TRAIL in LC, rhTRAIL (AMG 951), Mapatumumab (anti-TRAIL-R1 mAb), and AMG 655 have been developed to target the death receptor in the lungs [32].…”
Section: Pi3k/akt/mtor Signaling Pathway and Pi3k/akt/mtor Inhibitors In Lcmentioning
confidence: 99%